Prevalence, comorbidities and mediators of childhood anxiety disorders in urban Turkey: a national representative epidemiological study - Mutluer, T.; Gorker, I.; Akdemir, D.; Ozdemir, D. Foto; Ozel, O. Ozcan; Vural, P.; Ercan, E. S. (Springer Heidelberg, 2023)
Purpose The aim of this study is to evaluate the prevalence of anxiety disorders, its correlation with sociodemographic characteristics, its comorbidities with other psychiatric disorders and its predictors in school-aged children. Methods This study is part of a representative, multi-centered national study that is planned by the Turkish Association of Child and Adolescent Mental Health to evaluate the prevalence of psychopathology among elementary school students in Turkey between the years 2014-2015. Children are screened via Kiddie Schedule for Affective Disorders and Schizophrenia for School Age Children Present and Lifetime Version. Impairment is assessed by a 3-point Likert type scale independently by the parent and the teacher. The final sample included 5842 children with the mean age of 8.7 years. Results The prevalence of any anxiety disorder without considering impairment is 16.7% and considering impairment is 5.2% in children according to our study. We found significant differences for comorbid Attention Deficit Hyperactivity Disorder, Disruptive Behavior Disorder, Mood Disorders, Tic Disorders, Obsessive Compulsive Disorder, Enuresis Nocturna, Encopresis, and Intellectual Disability. Having a history of paternal physical disorder, living in the regions of Marmara, Mediterranean and Black Sea were found to be the main predictors of having childhood anxiety disorders according to the logistic regression analysis. Conclusion Better understanding of childhood anxiety disorders, comorbid conditions and predictors will result in earlier diagnosis and more appropriate treatment.
Keywords: Childhood anxiety; Comorbidity; Prevalence; Epidemiology